E-Commerce Web Based Application for UMKM Products of Rejowinangun Village, Kademangan District, Blitar Regency - Chrystia Aji Putra; Ronggo Alit; Yisti Vita Via (Future Science)
Desa Rejowinangun is one of villages located in Kecamatan Kademangan, Kabupaten Blitar. This village has potential in form of Micro, Small and Medium Enterprises. In this village, majority of population make a living as traders or entrepreneurs, so that Desa Rejowinangun is dubbed as UMKM Village. Many of real problems faced by UMKM actors in this village. Most important problem is related to marketing of UMKM products. Business people in Desa Rejowinangun are still relying on conventional methods of carrying out marketing business so far. Using conventional sales model, many UMKM sell their products indirectly to consumers, but through orders or requests from distributors or stores. Production of UMKM, which were mostly sold to second hand, made UMKM not maximal in gaining production profits because profits had to be shared with second hand distributors. Marketing methods carried out until now still use social media such as Instagram, Tokedia and Shoope. Marketing methods through social media have a more limited reach, which can only reach audiences that are connected to the internet and access social media, so that the marketing of these entrepreneurial activists is better and the reach is wider then the idea to develop and change towards digital marketing where one of them is through a media website, a special website will be built to shelter UMKM actors, especially UMKM in Desa Rejowinangun to market their products.UMKM will have advantage of using information technology to increase economic value of UMKM in this village, which is expected to increase income and added value to Desa Rejowinangun as a UMKM village.